Ferumoxytol‐enhanced magnetic resonance T1 reactivity for depiction of myocardial hypoperfusion. (8th April 2021) - Colbert, Caroline M.; Le, Anna H.; Shao, Jiaxin; Currier, Jesse W.; Ajijola, Olujimi A.; Hu, Peng; Nguyen, Kim‐Lien
Abstract : Myocardial T1 reactivity, defined as the relative change in T1 between rest and vasodilator‐induced stress, has been proposed as a magnetic resonance imaging (MRI) biomarker of tissue perfusion. We hypothesize that the superparamagnetic iron‐oxide nanoparticle, ferumoxytol, sensitizes T1 to changes in the intramyocardial vascular compartment and improves the sensitivity and specificity of T1 reactivity as an imaging biomarker of tissue perfusion. We aim to assess the diagnostic performance of ferumoxytol‐enhanced (FE) myocardial T1 reactivity in swine models of myocardial hypoperfusion. We induced acute myocardial hypoperfusion in 13 swine via percutaneous, transcatheter deployment of a 3D printed intracoronary stenosis implant into the left anterior descending coronary artery. We performed native and FE adenosine stress testing using 5(3)3(3)3 MOLLI and SASHA T1 mapping sequences with bSSFP readout on a clinical 3.0 T magnet. MOLLI T1 maps were fitted using both the conventional MOLLI and the Instantaneous Signal Loss (InSiL) T1‐fitting algorithms. Regardless of the MOLLI or SASHA pulse sequence or T1‐fitting algorithm, ferumoxytol contrast increased the dynamic range of T1 reactivity in both the remote and ischemic myocardial regions. Relative to remote myocardium, native and FE T1 reactivity were blunted in ischemic myocardium ( p < 0.05) with InSiL‐MOLLI, MOLLI and SASHA. An InSiL‐MOLLI–derived FE T1 reactivity threshold of −4.65% had 73.3% sensitivity and 96.2% specificity for prediction of regional wall motion abnormalities (AUC 0.915, 95% CI 0.786–0.979), whereas a SASHA‐derived FE T1 reactivity threshold of −5.25% had 75.0% sensitivity and 95.2% specificity (AUC 0.905, 95% CI 0.751–0.979). Ferumoxytol significantly increased the dynamic range of T1 reactivity as a measure of myocardial hypoperfusion in vasodilator stress T1 mapping studies. FE T1 reactivity maps can be used to quantitatively distinguish ischemic and remote myocardium with high specificity in swine models of acute myocardial hypoperfusion. Abstract : We performed native and ferumoxytol‐enhanced (FE) MRI stress testing in 13 swine with acute stenosis in the left anterior descending coronary artery using T1 mapping pulse sequences at 3.0 T, and computed myocardial T1 reactivity. Ferumoxytol increased the dynamic range of T1 reactivity, potentially improving the sensitivity of T1 reactivity as a measure of tissue perfusion. FE T1 reactivity maps can be used to distinguish ischemic myocardium (white arrows) from remote myocardium with high specificity.